análisis de las propiedades psicométricas del cuestionario de trauma infantil (ctq-sf) en una muestra de adultos colombianos (2017)
The present research shows results of the analysis of the psychometric properties of the Childhood Trauma Questionnaire in the adult population of the city of Bogotá, Colombia. For this purpose, 454 people from the city of Bogotá, aged 18 and over, participated by answering the questionnaire. At the outset, the relevance of working with standardized measurement instruments in the Colombian or, to a greater extent, Latin American context is highlighted. Also I know mentions the difficulty of working with the term 'trauma' and proposes the term 'traumatic events' instead.